Groundwater quality testing in the area of municipal waste landfill sites in Dąbrowa Górnicza (southern Poland) - Łukasik Martyna; Dąbrowska Dominika (Environmental & Socio-economic Studies, 2022)
Groundwater quality assessment for pollution can be undertaken with the use of indicators that will confirm or deny the negative impact of potential pollution sources. Based on water quality monitoring data from the Lipówka I and Lipówka II municipal landfill sites in Dąbrowa Górnicza from the last five years, the water quality in the area was assessed using the Nemerow Pollution Index (NPI) method. Seven parameters were assessed – pH, electrical conductivity, and the concentrations of chlorides, sulphates, ammonium ions, boron and iron. The limits for class III water quality were used as the reference level. The results of the NPI calculations show that the highest indices were obtained for the piezometers PZ5 and T5 located in the outflow of the water from the Lipówka I landfill site. The highest values of the Nemerow index were obtained for ammonium ions and reached a value of over 36 in the PZ5 piezometer and 17 in the T5 piezometer. The other parameters did not indicate a significant impact of the landfill sites on the quality of groundwater. The highest values of the indicators were observed in 2017. It is worth noting that, apart from the large differences in the content of ammonium ions, the values of the Nemerow indices for the electrical conductivity specifically for the PZ5 piezometer are twice as high as for the other piezometers and four times higher than for boron. The Nemerow index is a useful and easy method of assessing the quality of groundwater. It can even be used for a small number of parameters.